2014
DOI: 10.1097/lbr.0000000000000079
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Cryobiopsy in Diagnosing Carcinoid Tumors

Abstract: Cryotherapy probe biopsy should be considered a safe and effective approach to diagnose carcinoid tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Although the safety of flexible bronchoscopic biopsy is controversial, some investigators have reported cases of serious bleeding. Recently, the usefulness of cryobiopsy for diagnosing carcinoid, which provides larger and higher quality specimens than conventional forceps biopsy, has been reported (Boyd et al 2014;Gao et al 2020). However, it is likely associated with a higher frequency of bleeding complications.…”
Section: Discussionmentioning
confidence: 99%
“…Although the safety of flexible bronchoscopic biopsy is controversial, some investigators have reported cases of serious bleeding. Recently, the usefulness of cryobiopsy for diagnosing carcinoid, which provides larger and higher quality specimens than conventional forceps biopsy, has been reported (Boyd et al 2014;Gao et al 2020). However, it is likely associated with a higher frequency of bleeding complications.…”
Section: Discussionmentioning
confidence: 99%
“…During the initial procedure, tumor biopsy was taken for histologic confirmation, either by means of cryoextraction (achieved by rapid withdrawal of the cryoprobe after freezing part of the lesion for ∼3 s or until evidence of visible freezing) or with the use of biopsy forceps, depending on individual operator’s clinical judgment and/or preference. In general, we advocate the use of cryoprobe extraction over biopsy forceps, because it reduces the risk of yielding small specimen samples with severe crush artefacts in which mitotic count may be difficult to evaluate 16–18. Intraoperative bleeding occurring at the tumor site was controlled with boluses of 10 ml of adrenaline 1:100,000 solution and/or use of the cryoprobe at the bleeding point.…”
Section: Methodsmentioning
confidence: 99%
“…In general, we advocate the use of cryoprobe extraction over biopsy forceps, because it reduces the risk of yielding small specimen samples with severe crush artefacts in which mitotic count may be difficult to evaluate. [16][17][18] Intraoperative bleeding occurring at the tumor site was controlled with boluses of 10 ml of adrenaline 1:100,000 solution and/or use of the cryoprobe at the bleeding point.…”
Section: Cryotherapy Proceduresmentioning
confidence: 99%
“…98 Several studies have confirmed these findings, 103 including the safety in the diagnosis of carcinoid tumours. 104 Peripheral lung lesions Schumann et al evaluated the accuracy in the diagnosis of peripheral lesions with the guidance of rEBUS: the diagnostic yield of 74.2% was not significantly higher in comparison with that of EBUS-guided forceps biopsy (61.3%); however, samples were significantly larger than those collected by TBB. 105 Other studies showed a diagnostic yield of 69---85% when guided by ultrasounds or EMN, and confirmed the advantage of larger samples and a better preserved architecture, thus improving the specimen quality for the molecular diagnosis.…”
Section: Endobronchial Lesionsmentioning
confidence: 99%